Persistent Aneurysm Growth Following Pipeline Embolization Device Assisted Coiling of a Fusiform Vertebral Artery Aneurysm: A Word of Caution! - Mena Kerolus; Manish K. Kasliwal; Demetrius K. Lopes (Neurointervention, 2015)
The complex morphology of vertebrobasilar fusiform aneurysms makes them one of the most challenging lesions treated by neurointerventionists. Different management strategies in the past included parent vessel occlusion with or without extra-intracranial bypass surgery and endovascular reconstruction by conventional stents. Use of flow diversion has emerged as a promising alternative option with various studies documenting its efficacy and safety. However, there are various caveats associated with use of flow diversion in patients with fusiform vertibrobasilar aneurysms especially in patients presenting with acute subarachnoid hemorrhage (SAH). We report a rare case of persistent aneurysmal growth after coiling and placement of the Pipeline Embolization Device (PED; ev3, Irvine, California, USA) for SAH from a fusiform vertebral artery aneurysm. As consequences of aneurysm rupture can be devastating especially in patients with a prior SAH, the clinical relevance of recognizing and understanding such patterns of failure cannot be overemphasized as highlighted in the present case.